2016
DOI: 10.1142/s1793431116400078
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance Evaluation and Strengthening of RC Frames with Substandard Beam-Column Joint: Lessons Learned from the 2013 Bohol Earthquake

Abstract: On October 15, 2013, a magnitude 7.1 earthquake severely damaged buildings on Bohol Island, the Philippines. This paper briefly reports on the typical damage to reinforced concrete (RC) buildings observed in the authors’ post-earthquake investigation. The current study focuses on the seismic performance of an earthquake-damaged building with exterior beam-column joint failure. Cyclic loading tests were conducted to propose a practical seismic strengthening method by installing RC wing walls for substandard mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…However, this assumption may mislead the analysis results in the case of substandard beam-column joints, because the failure of the joint may occur as confirmed in the literature of experimental studies (e.g. [1], [2], [10]- [12]) and an experimental study by one of the authors [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption may mislead the analysis results in the case of substandard beam-column joints, because the failure of the joint may occur as confirmed in the literature of experimental studies (e.g. [1], [2], [10]- [12]) and an experimental study by one of the authors [3].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Additionally, such poorly detailed joints still exist in newly constructed buildings in an area affected by a recent earthquake, 1 as observed in a field survey by two of the authors. Recent earthquakes in developing countries have revealed that severe damage or collapse of RC buildings is often caused by poor performance of the beam-column joints with substandard detailing.…”
Section: Introductionmentioning
confidence: 99%
“…Many buildings exist in developing countries potentially contain improper structural details which do not adequately meet requirements and/or recommendations according to the design guidelines [1][2][3][4][5] . As a result, such buildings in several developing countries have suffered from severe damage under sudden earthquakes.…”
mentioning
confidence: 99%
“…Beam-column joints are a critical link in modern moment-resisting RC structures. Recent seismic events [3][4][5] globally have highlighted the vulnerability of the beam-column joints, often resulting in severe damage. In developing countries like Bangladesh, the beam-column joints are even more susceptible to damage/total failure due to the following practical background.…”
mentioning
confidence: 99%